The Influence of Presentation of Financial Statements, Accessibility, Functional Oversight, Competence of Human Resources, and Internal Control Systems on the Accountability of Village Financial Management - Ifna Aisyatun Novalia; Aida Nahar (Accounting Study Program, Faculty of Economics and Business, 2022)
The study aims to know the effects to the presentation of financial statements, accessibility, functional supervision, human resources competence, and internal control systems for village accounting management. The population and samples from this study are residential communities in Jepara distric. The method of analysis used is a quantitative descriptive analysis. Whereas the analytical tools in the study use IBM SPSS 25. The analysis used in this study is instrument testing, classic assumption testing, linear regression analysis, test F, test T, and coefficient determinations. Research shows that the presentation of financial statements and internal control systems has positive and significant effects on village financial management accountability. While accessibility, functional supervision, and competence of human resource have no effects on village financial management accountability